2021
DOI: 10.21448/ijsm.861904
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Phenolic Composition, Antioxidant Capacity, and Antidiabetic Effect of Ornithogalum lanceolatum L.: An in vitro Study

Abstract: Diabetes Mellitus is a global health problem that leads to macro-and microvascular diseases associated with hyperglycemia. Phytotherapy is one of the alternative ways to cope with this type of disease. The genus Ornithogalum is consumed as a wild edible plant and traditionally used for ailments. This study aims to investigate the phenolic composition using High-Performance Liquid Chromatography as well as antioxidant and antidiabetic effects using spectrophotometric method of Ornithogalum lanceolatum L. aerial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In the literature, there are studies investigating the phytochemical content of Ornithogalum species. Temiz 26 carried out the phytochemical analysis of Ornithogalum lanceolatum extract distributed in Mersin (Turkey) by HPLC and reported that especially the leaf parts contain intense amounts of procateuic acid, rutin, quercetin and gallic acid.
Figure 3 LC–MS/MS chromatograms of O. umbellatum extracts.
…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are studies investigating the phytochemical content of Ornithogalum species. Temiz 26 carried out the phytochemical analysis of Ornithogalum lanceolatum extract distributed in Mersin (Turkey) by HPLC and reported that especially the leaf parts contain intense amounts of procateuic acid, rutin, quercetin and gallic acid.
Figure 3 LC–MS/MS chromatograms of O. umbellatum extracts.
…”
Section: Resultsmentioning
confidence: 99%
“…In the species O. armeniacum and O. lanceolatum the major phenolic components found were (+)-catechin and gallic acids [ 29 ]. In a latter study [ 14 ], it was found that in ethanolic extracts of O. lanceolatum protocatechuic acid was the main compound in both plant parts (aerial and bulbs) and that rutin, quercetin, and p -coumaric acid were the most predominant phenolic compounds in the aerial parts. Concerning the species O. narbonense , the major phenolic compounds were benzoic acid, p -hydroxybenzoic acid, chlorogenic acid, rutin, and caffeic acid [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are previous studies regarding the chemical profile and antioxidant activity of Ornithogalum , to which C. reverchonii was considered to belong until 2001 [ 11 ]. For instance, the phenolic profile composition and bioactivity of O. sigmoideum , O. orthophyllum , O. oligophyllum , O. lancelatum, and O. narbonense have been reported [ 12 , 13 , 14 ]. However, this work is the first report in the literature studying the phytochemical composition and biological activity of the genus Cathissa .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is necessary to investigate alternative medicines or natural treatment methods to overcome such side-effects of current drugs. There are many studies in the literature describing the antidiabetic activity of plant extracts (Temiz, 2021;Keskin et al, 2022). There are investigations depicting that pomegranate (Alsataf et al, 2021) and Quercus infectoria (Başyiğit et al, 2020) display antidiabetic activity.…”
Section: Antidiabetic Activities Of Free Esterified and Bound Phytoch...mentioning
confidence: 99%